Adaptive mesh axi-symmetric simulation of droplet impact with a spherical particle in mid-air. (October 2022) - Yoon, Ikroh; Chergui, Jalel; Juric, Damir; Shin, Seungwon
Highlights: Droplet-particle collision in mid-air is numerically investigated. A wide range of collision conditions (a total of 90 collision cases) is considered. Outcome regime maps and underlying physical mechanisms are thoroughly analyzed. Collision in mid-air is significantly different from that on a stationary particle. Abstract: In this study, droplet-particle collisions in mid-air are numerically investigated for a wide range of collision parameters: Weber number, contact angle and droplet/particle diameter ratio (4 ≤ We ≤ 150, 20° ≤ θ eqi ≤ 160°, and Ω = 1/2 and 1). To perform these simulations in an efficient manner, a simple dual grid based adaptive mesh refinement (SDG AMR) strategy is proposed and implemented in our existing multiphase flow solver. A total of 90 collision cases are systematically analyzed and are compared with results for the case of impact on a stationary particle to understand how mid-air collision characteristics are changed relative to those on a stationary target. The simulation results show that mid-air droplet-particle collision behavior is significantly different from that of droplet collision on a stationary particle, thus the impact phenomena cannot be interpreted by extrapolating collision results for a stationary target.